Design Prototype Detector of Temperature, Humidity, and Air Quality using Sensors, Microcontrollers, Solar Cells, and IoT - Jacquline Waworundeng (CogITo Smart Journal, 2023)
Environment monitoring refers to the process, tools, and techniques to observe the quality of the environment. This research discussed the prototype detector of temperature, humidity, and air quality in a scope of hardware design. The components consist of sensors, and microcontrollers with electricity and solar cells as power supplies. The sensors used a DHT22 as the temperature and humidity sensor module and the MQ135 air quality sensor module which are connected to two types of microcontrollers, namely Arduino Uno R3 and Wemos ESP32 for data processing. The prototype has a Wi-Fi modem that can provide a connection to the internet. This prototype can be used as a tool to detect and monitor the environmental changes related to temperature, humidity, and air quality whether indoors or outdoors. The prototype is designed to be integrated with IoT platforms so that data can be sent to the smartphones and then viewed by the users. With the support of the IoT platform, the value of temperature, humidity, and air quality can be monitored easily in a real-time. This design of prototype, potentially be implemented indoors or outdoors to observe the changes in the environment.